Digital Transformation : Workshop on Using AI to Improve Teacher Competency - Wenty Zahrati; Yetty Sembiring; Ardiensyah; Elvira Mulya Nalien; Fitri Yul Dwi Marta; Arina Romarina; Rozali Ilham; Asmungi (Civitas Consecratio: Journal of Community Service and Empowerment, 2025)
Advances in science and technology have brought significant changes to the world of education, one of which is the development of Artificial Intelligence (AI), which can be utilized to improve the learning process. This article is the result of a community service activity carried out by the IPDN West Sumatra Campus Lecturer Team in collaboration with the Education Office, which aims to improve the understanding of teachers and teaching staff throughout Payakumbuh City about the role of Artificial Intelligence (AI) in education. The knowledge transformation was carried out in the form of a technology workshop where the material was presented using lectures, discussions, and direct practice methods. This workshop focused on the use of ChatGPT and Gamma Ai as interactive learning media. Attended by 75 elementary and junior high school teachers and teaching staff. The results of this workshop showed that 95% of participants understood the use of ChatGPT and 90% mastered Gamma Ai. It is hoped that this article will serve as a foundation for teachers and teaching staff to be able to utilize Artificial Intelligence (AI) technology in future learning practices.